Organizações e desenvolvimento local: o papel dos atores locais nos municípios de Assis Chateaubriand e Palotina - Pr - Denuzi, Vanessa Stafusa Sala (2012)
The purpose of this research was analyzing the role of organizations in the local development, using a comparative study between Assis Chateaubriand and Palotina cities, located in Western Parana State. The fact that these cities have developed unequally cannot be attributed only to causality, so it is discussed how the behavior of local agents interferes in the locality s development. Based on the hypothesis that the more participation of local agents by their representative organizations the higher economic local development tends to be, fact which would explain the economic advance of Palotina city in relation to Assis Chateaubriand city. Regarding methodological procedures, comparative study was used and based on the theoretical references the main determinants to local development were grouped. From these determinants, an applied interview guide was created in an intentional sample of organizations representing the civilian society of both cities. In order to ensure the representativeness of different types of organizations, they were listed in political, economic and social organizations. The research concluded that economic organizations of Palotina city, even with lower population and territory area than Assis Chateaubriand city, were the most determining to making the city more dynamic and more attractive to capital. The main organizations that stood out in this city were the Agroindustrial Cooperative C.Vale and Federal University of Parana (UFPR), as entrepreneurial company and research center, respectively. In Assis Chateaubriand, the political, economic and social organizations have articulated so the city could improve. An example of such improvement was the mobilization to the establishment of the Federal Institute of Parana (IFPR), as a center to form qualified manpower.